Evidence based medicine in clinical practice: how to advise patients on the influence of age on the outcome of surgical anterior cruciate ligament reconstruction: a review of the literature. Issue 3 (1st June 2002) - Sloane, P A; Brazier, H; Murphy, A W; Collins, T
Abstract : Objective: To determine, using a literature search, whether patient age influences the outcome of surgical reconstruction of a torn anterior cruciate ligament. Methods: Medline (1966 to present) was searched using the PubMed interface, Embase (1974 to present) using the Datastar system, and the Cochrane Library at the Update Software web site. Papers retrieved from the three databases were independently assessed by two reviewers using preliminary inclusion criteria. Reference lists of papers satisfying the preliminary criteria were then scanned and appropriate papers reviewed. Any new papers in turn had their reference lists scanned, this process continuing until no new papers were identified. Final inclusion criteria were then applied to all papers satisfying the preliminary inclusion criteria. Results: The initial search identified 661 papers. Exclusion of duplicates produced 536 unique papers. Medline contained 445, Embase 185, and the Cochrane Library 31. Of the 536, 523 were assessed by abstract and 12 by full text; one paper was not retrieved. Application of the preliminary inclusion criteria produced 33 papers. Their reference lists contained 950 references. Scanning of these added six new papers to the dataset. These six had their reference lists assessed; no new papers were identified. Four of the 39 papers in the completed dataset satisfied the final inclusion criteria. There was wide variation in the total number of subjects in the four studies, ranging from 22 to 203 patients. The total number of different outcome measures was 17; only one measure was used by all four studies. None of the objective outcome measures showed any significant difference between age groups, and the subjective measures, which did show differences, were contradictory. A total of 108 interlibrary loans were requested, by a full time researcher, at a total cost of IR£432.00 over a 10 week period. Conclusions: When advising patients on the outcome of anterior cruciate ligament reconstruction, age should not be considered in isolation. In the absence of relevant guidelines, meta-analyses, or systematic reviews, the application of evidence based medicine to clinical practice has significant resource implications.